Exploring the effect of autonomy and psychological well-being: a comprehensive analysis among IIUM students - Diab Al-Juneidi, Diaa Musa; Harvey Fontaine, Rodrigue Ancelot; Sharofiddin, Ashurov (World Academy of Islamic Management (WAIM), 2024)
This study examines the influence of autonomy on the psychological well-being of 289 undergraduate students from the Kulliyyah of Economics and Management Sciences at the International Islamic University Malaysia. Employing the psychological well-being (PWB) scale for autonomy, regression tests demonstrate positive effects on psychological well-being. Key findings indicate a significant effect between autonomy and enhanced psychological well- being among students. The implications of these results suggest the importance of fostering autonomy in educational and personal development initiatives for university students. Future research might want to see whether there are Islamic concepts in the Qur’an and the Sunnah that are similar to autonomy.